Culturally diverse teams and inter-organizational knowledge sharing behavior: The role of perceived morality and relationship orientation - Nguyen, M.; Sharma, Piyush; Kingshott, Russel; Malik, A. (2024)
This paper draws on social exchange and social capital theories to explore knowledge-sharing behavior with culturally diverse teams from business-to-business (B2B) partners. We use two experimental studies to examine the direct effects of cultural diversity between B2B partners and its indirect effects through perceived morality on their knowledge-sharing behavior, along with the moderating effect of B2B relationship orientation on the link between cultural diversity and their KSB. Using a behavioral measure of knowledge-sharing behavior, this paper extends the B2B relationships literature by highlighting the value that intercultural relationships bring to these relationships. In addition, the results provide managers with a range of strategies in managing culturally diverse teams, such as leveraging their B2B relationship orientation directed towards culturally diverse teams from partner firms to improve knowledge sharing with them.